FridaysForFuture as an Enactive Network: Collective Agency for the Transition Towards Sustainable Development - Francesconi, Denis; Symeonidis, Vasileios; Agostini, Evi (Frontiers in education (Lausanne), 2021)
In this article, we provide a theoretical conceptual analysis of FridaysForFuture (FFF) and of its effort in promoting the governance of socioeconomic transition toward sustainable development. FFF is a social movement that has received outstanding public recognition and visibility across the world in the last 2 years and is of great interest to educational research because it is largely composed of youngsters and appears to play a paideutic role in societal innovation. There is a growing but still limited body of investigation of FFF’s structures, genealogy, and behavior. The same goes for its theoretical and ethical background and principles. Its efforts to promote social change by going beyond individual agency toward collective agency deserve greater attention from educational scientists. We argue that FFF is a complex, self-organizing, informal network, which we define as an enactive network for its ability to retrieve scientific knowledge and transform it into lived meaningful knowledge, and for its capacity to mobilize masses and influence public discourse under a specific ethical umbrella. We provide six macro categories to describe and explain FFF: 1) nested emergent network, 2) collective social agency and leadership, 3) political impact, 4) science-based learning and activism, 5) paideutic function, and 6) ethical (normative) stance. We stress the FFF capacity to recruit high-level scientific knowledge without direct support from schools, and embody strong ethical stances with specific references to the ethics of responsibility and care for the interaction between humanity and the natural world. Finally, we suggest that FFF can be interpreted as an enactive network with the ability to affect collective identity and empower collective agency by encouraging communities into a more scientific, evidence-based, and ethical public discourse.